2022
DOI: 10.1002/jsfa.12250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post‐silking drought stress degree on grain yield and quality of waxy maize

Abstract: BACKGROUND Drought stress (DS) induced by post‐silking have a major impact on the yield and quality of maize. In this study, the effects of different degrees of DS after pollination on grain filling, starch and protein metabolism, and functional properties were investigated using two waxy maize cultivars as materials. The levels of DS that were investigated were ‘mild water stress’ (WS1), ‘moderate water stressed’ (WS2), and ‘severe waterstressed’ (WS3). RESULTS Drought stress decreased grain fresh weight, dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…Debon et al (1998) and Silva et al (2001) found that the increase in the starch concentration of fresh fruit of potato was mainly due to the concentration effect caused by the decrease in water content in fresh fruit. Guo et al (2022) and Shi et al (2018) also showed an increase in starch content in fresh waxy maize grains under drought stress and indicated that acceleration of grain filling and decreases in grain water content under drought (Figure 7F) might be the main reasons for the starch content increase. Meanwhile, water deficit caused a significantly increase in abscisic acid (ABA) content in maize plant tissues, and then led to the activity increases of four key enzymes related closely to converting soluble sugar into starch (Zhang et al, 2012).…”
Section: Effects Of Water Deficits At Different Growing Stages On Gra...mentioning
confidence: 87%
See 2 more Smart Citations
“…Debon et al (1998) and Silva et al (2001) found that the increase in the starch concentration of fresh fruit of potato was mainly due to the concentration effect caused by the decrease in water content in fresh fruit. Guo et al (2022) and Shi et al (2018) also showed an increase in starch content in fresh waxy maize grains under drought stress and indicated that acceleration of grain filling and decreases in grain water content under drought (Figure 7F) might be the main reasons for the starch content increase. Meanwhile, water deficit caused a significantly increase in abscisic acid (ABA) content in maize plant tissues, and then led to the activity increases of four key enzymes related closely to converting soluble sugar into starch (Zhang et al, 2012).…”
Section: Effects Of Water Deficits At Different Growing Stages On Gra...mentioning
confidence: 87%
“…The reduction of photosynthetic rate under water deficit may lead to a reduction of plant photoassimilate deposition and ultimately the loss of grain yield ( Kimaro et al., 2015 ; Ye et al., 2020a ; Ulfat et al., 2021 ). Previous studies have shown that a water deficit during grain filling reduced the grain fresh weight, water content, and grains per ear of waxy maize ( Guo et al., 2022 ). In this study, fresh ear yield with husk and fresh ear yield were significantly reduced, and the grain number per ear and 100-grain weight also showed some reducing trends under the D V6–VT and D VT–R2 treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in meteorological factors caused by the sowing date is the main reason for the change in maize grain quality. The grain-filling period is the key stage for maize grain quality, especially for endosperm cells and starch granule formation [22], which is sensitive to environmental adversity [23]. According to the VIP value between meteorological conditions and the main nutritional quality during the whole growing period, it was found that although environmental factors are the key factors affecting grain quality trait, there are differences in the starting point of the key stage and the duration of the key stage (Figure 3).…”
Section: Optimization Of Both Key Stage and Corresponding Meteorologi...mentioning
confidence: 99%
“…Moreover, due to their high reactivity, excess ROS are hazardous and can destroy nucleic acids, proteins, and lipids [ 5 ]. In addition, severe drought stress could reduce yield and quality, which in turn affect real productivity [ 6 ].…”
Section: Introductionmentioning
confidence: 99%